Hibernation - Sander van Wettum - Wettum, Sander van (The Eriskay Connection, 2021)
Hibernation is a well known phenomenon in the natural world: a seasonal state of minimal activity, as an adaptation to winter conditions. But also man-made places can enter this dormant state between dream and reality.00Since World War II, the construction of mass tourist locations has been unceasing. Within just half a century, the sun drenched coastlines of Southern Europe were transformed into a global tourist destination. The resulting agglomeration of overdeveloped beach towns no longer show any recognisable relationship with their surroundings, country and history. During the winter, these towns go into hibernation. Tourists disappear, hotels, bars and restaurants close up.00'Hibernation' is an exploration into the off-season state of these places. A journey along surreal architecture, spaces and atmospheres, photographed at moments when their intentional context of use has dissolved and new realities appear. Sander van Wettum?s (NL) photographs invite the viewer to project their own narratives, memories and dreams upon the ambiguous scenery presented, while at the same time showing the harsh and absolute consequences of mass tourism.00Including a fact-fiction story by David Richardson, a British journalist specialised in the travel industry